Rancang Bangun Game Edukasi Berbasis Android 2D "Nawa Sanga" dengan Penerapan Multimedia Development Life Cycle (MDLC) - Lakzmi, Prita Patricia; Prasetya, Renaldi Primaswara; Wahyuni, Febriana Santi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The advancement of technology has made video Games an effective educational tool. This research aims to design and develop a 2D educational Game for Android, Nawa Sanga, which integrates elements of Indonesian history with interactive Gameplay. The method used is the Multimedia Development Life Cycle (MDLC), encompassing the stages of conceptualization, design, material collection, production, testing, and distribution. Each level of the Game features historical sites in Indonesia, where players take on the role of Nawa, protecting historical sites from enemy threats while learning history through interactive educational pop-ups. Testing results indicate that 47% of 28 users rated the graphic quality and visual design, as well as the Game’s effectiveness as a historical educational medium, as excellent, while 41% rated it good. The Game proved effective in helping players learn about Indonesian history with easy-to-use controls. Nawa Sanga is expected to help younger generations understand and preserve Indonesia's historical heritage.